Economic and ecological trade-offs of coastal reclamation in the Hangzhou Bay, China. (June 2021) - Qiu, Lefeng; Zhang, Min; Zhou, Bibing; Cui, Yuanzheng; Yu, Zhoulu; Liu, Tao; Wu, Shaohua
Highlights: Coastal reclamation in Hangzhou Bay from 1985 to 2015 were explored. Land reclamation has greatly degraded ecosystem service value of coastal wetlands. Economic gain failed to compensate for ecosystem service value loss in coastal reclamation. The strict prohibition on coastal reclamation poses a big challenge to local governments. Abstract: Due to the growing demand for land resources, coastal reclamation has become a global land use practice. Although the reclamation of coastal wetlands brings substantial economic benefits, it can lead to a series of adverse ecological impacts. Considerably, economic and ecological trade-offs of reclamation activities must be analyzed to make targeted land use policy decisions. This study focuses on land reclamation on the east coast of China, taking Hangzhou Bay as a case study. Remote sensing techniques were used to detect the coastline and landscape changes in the reclaimed areas from 1985 to 2015. Subsequently, field surveys and empirical parameters were employed to evaluate the impact on coastal ecosystem services. Finally, the monetary analysis was used to evaluate the trade-offs between ecological loss and economic gain due to land reclamation. The results showed that a total of 75134.3 ha of coastal wetlands (accounting for 8.58% of the total land area) were reclaimed from 1985 to 2015 in the Hangzhou Bay. A substantial decline in ecosystem service value (ESV) was observed with a drop from 866, 400 Yuan ha −1 in 1985 to 285, 800 Yuan ha −1 in 2015 due to the conversion of natural to artificial landscape. The total ESV loss exceeded the economic benefits throughout the study period, thus the economic benefits failed to compensate for the ESV loss. This trade-off relationship resulted from reclamation expansion on short-term economic benefits at the expense of long-term ecological value. According to these findings, we propose three main ways to achieve a "win–win" situation between gains and loss of reclamation for sustainability.